O Jornalismo de divulgação científica e a constituição do lugar enunciativo da superinteressante - Rocha, Renata Ferreira dos Santos (2007)
This dissertation intend show how happen the constitution of the enunciative place from Superinteressante in the speech field of spready scientific detaching the way how the magazine position itself in relationship to the controversies set up in the speech feeld in what discuss the thematic of maintenance (or no) of the human life, in field of the journalism of spready scientific. From the notion of speech type from Bakhtin (2003), draw a some considerations about the report type of spready scientific, en the order to characterize, of way tining satisfactory, the regular instancity of the corpus of analysis, searching show how the controversies are placeds in scene in reports for the related speech. The purpose is verify how and in what measure the magazine don t itself position of impartial way in front of the discuss themes, in spite of fetch tirelessing construct a itself image how simple mediator of the approach questions, producing the what we call effect of position of neutrality. The corpus is form for three reports of cover from magazine: In the end, what is happening with the Medicine? (Year 15, n. 5, May / 2001), Vaccines: the cure or the illness? (Year 15, n. 2, February / 2001), and Euthanasia (Year 15, n. 3, March / 2001). The theoritical base is foundation in formulations from the three authores: Bakhtin (1986 / 1929), Authier-Revuz (2004) e Maingueneau (1997; 2005), more specific, in the notions of the dialogia , enunciative heterogeneity and interdiscuss. The approach of the corpus happen from the notion of controversie presentation for Maingueneau (2005).